Consequential cognition: Exploring how attribution theory sheds new light on the firm‐level consequences of product recalls. (29th January 2019) - Munyon, Timothy P.; Jenkins, Matthew T.; Crook, T. Russell; Edwards, Jonathan; Harvey, N. Paul
Summary: It is unclear why some firms suffer greater negative consequences than others following a product recall. To shed light on this question, we extend attribution theory to the firm level to explore how consumers engage in an attributional process following product recalls that shapes their responses to firms. Integrating attribution theory and the demand side theoretical perspective, we assert that consumer judgments of responsibility toward manufacturers are shaped by causal data regarding the locus of causality (i.e., manufacturer or supplier) and controllability (i.e., prior knowledge or awareness) of a recalled product's potential for harm. We then examine the impact of product recall characteristics on judgments of responsibility and firm‐level outcomes using an experimental test involving responses from 320 subjects. Our findings suggest that judgments of responsibility are attributed to the manufacturing firm more when consumers are given causal information indicating that the firm is the source of, or is aware of, a product's defects. The results also indicate that judgments of responsibility can have costly firm‐level consequences in the form of reputational damage, diminished consumer purchase intentions, and increased legal damage recommendations. We discuss theoretical contributions, practical implications, and opportunities for further research.